Well‐Dispersed and Size‐Controlled Supported Metal Oxide Nanoparticles Derived from MOF Composites and Further Application in Catalysis. Issue 26 (25th March 2015) - Liu, Hong; Zhang, Suoying; Liu, Yayuan; Yang, Zhuhong; Feng, Xin; Lu, Xiaohua; Huo, Fengwei
<x xml:space="preserve">Abstract</x> Supported metal oxide nanoparticles are important in heterogeneous catalysis; however, the ability to tailor their size, structure, and dispersion remains a challenge. A strategy to achieve well‐dispersed and size‐controlled supported metal oxides through the manageable growth of a metal organic framework (Cu–BTC) on TiO2 followed by pyrolysis is described.